Mapping Customer Engagement Research: A Bibliometric Analysis - Tanjung, Lutfiyanah; Damayanti, Dhea Ajeng; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to map research development on customer engagement (CE) comprehensively. This qualitative research conducts historical and bibliometric analysis of quality-standard scholarly articles published in leading international journals. CE has experienced significant growth in the last decade, especially in 2021. Bibliometric analysis was used to analyze articles from Elsevier, Emerald, Springer, Taylor Francis, and IEE databases. A search using Publish or Perish from 2007 to 2025 resulted in 621 articles. Co-occurrence analysis found 1,352 keywords derived from titles and abstracts. The occurrence of keywords is limited to 5; from the limitation of the occurrence, 69 keywords are divided into 8 clusters. Through visualization of research trends and author collaboration networks, bibliometric analysis is essential for developing CE research. This analysis resulted in various suggestions for additional research projects. The analysis results also help map the scientific landscape and determine the direction of future research on customer engagement. This study also emphasizes the shift of CE research from traditional marketing methods to digital engagement strategies. Highly cited works and influential authors were also identified, demonstrating an essential role in developing theory. In addition, new topics such as disengagement and problems in implementing CE strategies still need to be researched. Visualizations of overlay and density reveal how research priorities have changed over time and how specific key keywords dominate the literature. This study provides practical insights for academics and practitioners and offers a reference to identify research gaps, recent subjects, and development opportunities in customer engagement.